The problem of determining the eligibility of the electronic contractor through modern means of communication - رقاني عبد المالك; شوقي نذير (مجلة الاجتهاد للدراسات القانونية والاقتصادية, 2021)
This study aims at the most severe and difficult problems facing the online customer and is in the process of determining the eligibility of the electronic contractor in order to verify the eligibility of the contracting party, which is carried out through modern communication technologies and without the physical presence of the contractors, especially since a large number of Internet users are teenagers and young people. It happens that the minor seizes the credit card of one of his parents, or uses his electronic signature to perform some transactions on the network. As; The issue of determining the identity of the contracting person is one of the most prominent problems that arise in dealing with the Internet, and that is that the contract concluded through modern means of communication in accordance with the rules established in the civil law, like other contracts, is not valid unless it is issued by two contractors who have competence. Clearly determining the identity of both contractors. The implementation of each party’s obligations requires the beginning of its knowledge of the other party The fullness of eligibility may differ from one country to another, not to mention the fact that the Internet is a field subject to electronic piracy and foreign penetration, which leaves severe problems in the field of electronic contracting, the thing that distinguishes eligibility in the field of electronic contracting with a kind of privacy, making electronic environmental scientists seek to invent modern means To check eligibility.